AKT inhibitors in gynecologic oncology: past, present and future - Chen, Jinghong; Yin, Rutie (Frontiers in Oncology, 2025)
The PI3K/AKT/mTOR pathway serves as a critical signaling nexus in cancer, with AKT acting as a central regulator of tumor cell proliferation, survival, metabolism, and therapy resistance. AKT inhibitors show promising but variable anti-tumor activity in preclinical and clinical studies. Currently, multiple classes of AKT inhibitors—PH domain competitors (perifosine), allosteric inhibitors (MK-2206), and ATP-competitive agents (AZD5363, GSK2110183, GSK2141795, and GDC-0068) are under development, with several agents in phase II/III trials. While early results demonstrated encouraging response rates and prolonged PFS in selected patients, significant challenges remain. The efficacy needs confirmation in larger trials, toxicities require better management, and resistance mechanisms demand further elucidation to guide optimal therapeutic strategies. This study systematically reviews recent AKTi research in gynecological cancers, aiming to provide a theoretical foundation for identifying potential biomarkers, overcoming drug resistance, and developing prognostic models. These insights may further facilitate the clinical translation of key therapeutic agents.